Effect of Probiotic Giving on Digestive Function in Patients Post-Perforated Colorectal Cancer surgery - Hutapea, Impol; Bagus B.S.A, Ida; Alfianto, Untung (Indonesian Journal of Medicine, 2017)
Background: One of the goals of colorectal cancer surgery is to facilitate the digestive tract to function properly. Surgery performed can lead new problems such as infection, sepsis, postoperative pain, and nausea vomiting. ÃÂ Modulation of perioperative nutrition of intestinal microbiota such as probiotics is more and more applied as a strategy to reduce complications of elective surgical infection and accelerate the improvement of gastrointestinal symptoms such as flatus and defecation. The purpose of this study was to analyze the effect of giving probiotics on digestive function in patients after colorectal cancer surgery.Subjects and Methods: The subjects of this study were postoperative patients with colorectal cancer, with a total sample of 20. The sampling technique used non-random sampling. This type of the study is quasi experimental design with Post-test Only Control Design method. In this design, the sample is divided into two groups namely, group I was given probiotics and group II was not given probiotics then the follow up treatmen was conducted to assess the effect on the digestive function of patients after colorectal cancer surgery.Results: The majority of post-operative colorectal cancer patients were> 50 years (85%). The sex of post operative patients with colorectal cancer balanced between men and women, which was equally 50%. There was a significant difference between intestinal bowel surgery after colorectal cancer surgery which was given probiotics with no probiotics given (p <0.05). Similarly, post operative flatus colorectal cancer patients also had significant differences with the values (p <0.05). As for the defecation patients of post-surgery colorectal cancer , there was also a significant difference between the defecation patients of post-surgery of colorectal cancer surgery given probiotics and those not given probiotics with values (p <0.05).Conclusion: statistically, there was an effect of giving probiotics to digestive function including bowel sound, flatus, and defecation of post-surgery patient of colorectal cancer.Keywords: Probiotics, digestive function, colorectal cancerCorespondence:ÃÂ Impol Hutapea. Masters Program in Family Medicine, Sebelas Maret University. Email: papihamora@gmail.comIndonesian Journal of Medicine (2017), 2(2): 107-115https://doi.org/10.26911/theijmed.2017.02.02.05